DIGITAL PEDAGOGY BASED ON ARTIFICIAL INTELLIGENCE: TRANSFORMATION IN EDUCATION, STRATEGIES, AND INTERNATIONAL EXPERIENCE (World Bulletin of Education and Learning, 2025)
The rapid integration of artificial intelligence (AI) into educational ecosystems is shifting pedagogical paradigms from standardised to hyper-personalised, data-informed, and adaptive models. This article synthesises current evidence (2023–2025) on AI-driven digital pedagogy, examining three interconnected dimensions: (i) systemic transformations in teaching and learning processes, (ii) scalable and ethically grounded implementation strategies, and (iii) comparative insights from large-scale national and regional initiatives across Europe, North America, Asia, and the Global South.
Keywords: Artificial intelligence, digital pedagogy, personalised learning, teacher professional development, educational equity, comparative education policy, European Education Area.